TEACHING APPLICATIONS OF THE GENRE COURT SUMMONS IN GERMAN-SPANISH LEGAL TRANSLATION - Vigier Moreno, Francisco J. (2017)
This teaching experience was designed for and implemented in a university module on legal translator training in the German (as second foreign language or C language) - Spanish (first language or A language) language pair. It describes the applications of a simulated yet realistic project, whereby students were asked to translate a German court summons into Spanish. Following the main theories on textual genre (Borja, 2013; Orts, 2017), as applied to the pre-translation analysis of the communicative situation in legal translation (Prieto, 2013), trainee translators are able to develop their legal translation competence and to establish a decision-making framework (Way, 2014) that allows them to justify their solutions to the translation problems identified. Accordingly, they can continue their specialization in the translation of legal texts from German into Spanish with greater autonomy and self-confidence, by developing greater awareness of factors influencing the adequacy of decisions taken by the legal translator.